Social forces and politics in North East India - Baruah, Apurba K.; Gupta, Susmita Sen (Guwahati DVS Publishers, 2013)
Most of the papers presented at the national seminar on "Social Forces and Politics of Regionalism in North-East India", held at North-Eastern Hill University in March 2010
Includes bibliographical references (p. [251]-264) and index.